Reizdarmsyndrom – eine Krankheit - Andresen, Viola; Layer, Peter (DMW - Deutsche Medizinische Wochenschrift, 2018)
The irritable bowel syndrome (IBS) counts among the most prevalent chronic diseases. Clinically, the IBS is characterized by abdominal symptoms combined with irregular defecation, which are not explained by routine diagnostic tests. IBS is often triggered by enteric bacterial infections, and its pathogenesis involves disturbed enteric, gut-brain, and cerebral mechanisms. Diagnostic work-up must aim to establish a positive IBS diagnosis, and to exclude serious underlying differential diagnoses (such as neoplasia, inflammatory bowel disease, celiac disease and others). On the other hand, it is important to avoid diagnostic “overkill” including repetitive testing. Successful treatment of IBS usually combines unspecific basic (nutritional, psychological, lifestyle etc.) measures with specific, symptom-oriented medical therapy. Therapeutic efficacy is greatly enhanced by ruling out worrying diagnostic uncertainties (reassurance), and by initiating positive patient guidance.
Keywords: viszerale Hypersensitivität; Darmerkrankungen; Diarrhö; Obstipation; Bauchschmerzen